(untitled) (Fiep Bulletin - online, 2014)
Motor development is characterized as a constant change during the life of the individual, having its beginning at conception and ending with death. The aim of this study was, by means of evidence of motor Motor Development Scale, to evaluate the motor development in children sheltered in the Association for the Support Minor - COPAME, Santa Cruz do Sul, in order to diagnose which areas of greatest deficit and the overall rating of the motor development in the areas of fine motor and gross motor control. The study comprised 24 children in shelters, including 11 boys and 13 girls, aged 35 months and 132 months, project participants COPAME. Tests were conducted to evaluate the global and fine motor skills as well as laterality. The results showed that the children studied showed an IC motor development below, checking if a delay of 8.2 months for fine motor and 5.95 months for gross motor control in relation to chronological age. Regarding the profile engine, it was observed that more than 60% of children were classified with high normal motor age, average normal or low normal in tests of QM1 and QM2. However more than 20% were classified as lower or much less in both tests. As regards the handedness, it was found that 67% are defined laterally, however, preferably lateral varied. Handedness was undefined in 33% of children. It is thus to be adopted specific resources to restore motor age children through regular activities that allow the integral development of motor development.